ANALISIS TINGKAT KEBUGARAN JASMANI MAHASISWA PGSD SELAMA PANDEMI COVID-19 DITINJAU DARI KEMAMPUAN GERAK NON LOKOMOTOR - Arif Widodo; Safruddin Safruddin; Nasaruddin Nasaruddin; Radiusman Radiusman; Muhammad Sobri (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2020)
The Covid-19 pandemic forces all learning activities to be carried out online. College sports lessons are also conducted online. This study aims to determine the level of physical fitness of students during online learning during the Covid-19 pandemic. This research uses a quantitative descriptive approach. Data collection using a survey. The instrument used was a performing test. Indicators of student physical fitness can be seen from the non-locomotor motion of standing stork and sit and reach. The research sample was 30 students. Data analysis using descriptive statistics. The results showed that the physical fitness of students during the Covid-19 pandemic when viewed from their non-locomotor ability to move was in the poor category. This can be seen from the low results of student body balance and flexibility tests.